DAKWAH GUSDURIAN ATAS HETERODOKSI ISLAM: Formulasi Inklusif Menghadapi Islam "Sempalan" - Aldi Hidayat; Luthfi Raziq; Abd. Mun’em (Jurnal Studi Qur'an dan Tafsir, 2022)
Abstract Aswaja is the dominant Islamic sect in the world level, especially in Indonesia. This dominant position necessitates Aswaja's moderate, tolerant and inclusive attitude towards minorities, such as "splinter" Islamic ideas and movements. Unfortunetly, Aswaja's attitude towards these minor entities tends to be exclucive, even persecutive, as proven by the coercive elimination of the Shiite and Ahmadiyah sects. Through the MUI, this coercive elimination is becoming stronger, as evidenced by a series of physical attacks against these two groups and other groups deemed heretical. This attack is contraproductive to moderation as Aswaja's own doctrine as well as the character of national and state life. On that basis, I will elaborate on Gus Dur's thoughts about hereticy and how to respond it by ellaborating on the verses of the Qur'an along with the preaching verses in Q.S. al-Naḥl [16]: 125 uses Syaḥrūr ḥudūd theory. For this reason, this article will answer two problem formulations. First, what is the Qur'an conception about hereticy? Second, how does Gusdurian's preaching formula address other "deviant" groups? Regarding the first question, the article – by basing itself on the intepretation of Sunni scholars – finds that the deviant version of the Qur'an is aimed at non-Sunni groups. However, the Qur'an proposes three models of da'wah, none of which justifies violence either at the level of discourse, let alone physically. On the other hand, we must place deviant groups as dialogue partners, non an object of exclution and persecution. Keywords: Aswaja, Gus Dur, Da'wah, Hereticy, Tolerance